(untitled) (Web of Teachers: Inderscience Research, 2023)
Today, the effectiveness of education requires the analysis of the standard indicators of higher educational institutions, which reflect the qualitative characteristics of the use of modern technologies in the educational process. In this article, the importance of improving the pedagogical system and the successful application of pedagogical technologies to the educational process and the formation of a holistic view of the content of science, the main issues of using pedagogical technology elements that ensure coherence in mathematics education and the level of their solution are given.